Conflicts and reconciliations between the right to environment and the right to housing - Andrade, Júlia Luna; Gallo, Douglas (Technical and Scientific Journal Green Cities, 2021)
The present work addresses the relationship between the right to decent and quality housing and the right to a preserved and balanced environment in the context of contemporary cities. For this, environmental and housing issues will be addressed through historical data, analysis of laws, concepts and characteristics of urban development in the cities. Subsequently, based on the analysis of the various agents involved in the processes and under different perspectives, a reflection is made about the relationship between “human x nature” and its maintenance in the urban space, searching a model of urban development based on fullness is sought compliance with human rights for all sections of the population.  KEYWORDS: Nature and cit. Urban intervention paradigm. Housing issue. Urban planning.